2020
DOI: 10.4103/sjg.sjg_175_20
|View full text |Cite
|
Sign up to set email alerts
|

Disability and quality of life before and during the COVID-19 outbreak: A cross-sectional study in inflammatory bowel disease patients

Abstract: Inflammatory bowel disease (IBD) is a chronic disabling condition that negatively impacts on the physical, psychological, familial and social dimensions of those effected by it. [1] Furthermore, IBD has been found to be associated with psychological disorders, which lead to an impaired health-related quality of life (HRQoL) [2][3][4][5] as well Background/Aim: Inflammatory bowel disease (IBD) is a chronic disorder affecting patients' health-related quality of life (HRQoL) which adds to their disability. Little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
(43 reference statements)
2
25
0
Order By: Relevance
“…It has even been observed that many people who are sick do not go to the hospital for examination due to the fear of COVID-19 infection. Since sick people are more affected by COVID-19, those who are sick have more COVID-19 fear levels [ 51 , 52 , 73 ]. Similarly, more COVID-19 fear is felt when individuals have relatives or friends who have been infected by or died from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has even been observed that many people who are sick do not go to the hospital for examination due to the fear of COVID-19 infection. Since sick people are more affected by COVID-19, those who are sick have more COVID-19 fear levels [ 51 , 52 , 73 ]. Similarly, more COVID-19 fear is felt when individuals have relatives or friends who have been infected by or died from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Encountering or being contacting with infected people who do not show symptoms further increases this anxiety [ 49 , 50 ]. Many studies have found that people who have been sick frequently before COVID-19 are more likely to be adversely affected by COVID-19 [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Some studies have shown that individuals whose family or friends have become ill or have died because of COVID-19 have more stress, anxiety, and depression [ 50 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although research, with relatively small sample size, failed at identifying a negative impact of COVID-19 on the overall QOL among a population with in ammatory bowel disease, 9 another study demonstrated that patients with Parkinson's disease experienced worse mental health with lower QOL. 8 Around 20% of our respondents had a chronic disease and exhibited a lower QOL in the whole group and the workers' subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…6 Thus, COVID-19 is expected to affect the quality of life (QOL), de ned by the World Health Organization (WHO) as "an individual's perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards, and concerns". 7 However, data on the impact of COVID-19 on the QOL remain scarce, and only a few reports evaluated it among special populations, such as patients with pelvic oor disorders, 6 Parkinson's disease, 8 in ammatory bowel disease, 9 or among general practitioners working with suspected or con rmed cases on the frontline of COVID-19. 10 Another impact of the COVID-19 is the slowing down of major world economies with a higher risk for developing ones.…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainty about the Sars-CoV-2, itself and their job insecurity may affect the dietitians’ QoL. There are studies on patients’ QoL during the Sars-CoV-2 pandemic [ 13 , 14 , 15 , 16 , 17 ], but few among health professionals’ QoL during the pandemic [ 18 ]. Dietitians apply scientific knowledge about food and nutrition to promote optimal health outcomes to individuals, groups, and communities in health and disease states [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%